IMPROVING INCOME GENERATION IN OSUN STATE, NIGERIA: THE IMPORTANCE OF TRAINING TAX PERSONNEL FOR REVENUE ENHANCEMENT - Sajuyigbe, Ademola Samuel; Amusat, Adesola W; Fadahunsi, Adewale Charcles (Journal of Business And Entrepreneurship, 2023)
The aim of this study was to estimate the influence of training tax personnel on revenue generation, and also to determine the challenges of tax administration in Osun State, Nigeria. This study used a survey research design and collected data from 320 state tax officials using a structured questionnaire. Data analysis was performed using mean, chi-square, and path analysis. The results show that income generation is positively and significantly associated with tax officer training. This finding suggests that income generation is an indicator of tax officer training. The study also found that limited training programs, outdated manual systems, poor technical integration, lack of qualified personnel, lack of tax culture and taxpayer awareness, and lack of resources are the main challenges of tax administration in Osun State Nigeria. The findings of this study has significant policy implications, training tax personnel improves tax compliance, efficient tax administration, fair and equitable taxation, enhanced taxpayer services, increased revenue generation, and better stakeholder engagement. These implications can contribute to a more effective and trusted tax system, benefiting policymakers, taxpayers, and stakeholders alike. The study offers empirical evidence regarding the revenue structure within the state, serving as a basis for the establishment of effective tax policies. Additionally, this research is unique in its utilization of two theories, namely the diffusion theory of taxation and the human capital theory of taxation, to explore the education and motivation of tax collectors. It also highlights how various stakeholders, including tax administrators, policymakers, and civil society organizations, can benefit from the process of tax policy formulation and implementation.